Glycans as Modulators for the Formation and Functional Properties of Neutrophil Extracellular Traps: Used by the Forces of Good and Evil - Bornhöfft, Kim F.; Galuska, Sebastian P. (Frontiers in Immunology, 2019)
A very common mechanism to trap pathogens is the release of DNA. Like flies in a spider's web, pathogens are enclosed in a sticky chromatin meshwork. Interestingly, plants already use this mechanism to catch bacteria. In mammals, especially neutrophils release their DNA to prevent an invasion of bacteria. These neutrophil extracellular traps (NETs) are equipped with antimicrobial molecules, including, for instance, histones, antimicrobial peptides, lactoferrin, and neutrophil elastase. Thus, in a defined area, pathogens and toxic molecules are directly adjacent. However, several of these antimicrobial substances are also cytotoxic for endogenous cells. It is, therefore, not surprising that distinct control mechanisms exist to prevent an exaggerated NETosis. Nevertheless, despite these endogenous control instruments, an extraordinary NET release is characteristic for several pathologies. Consequently, NETs are a novel target for developing therapeutic strategies. In this review, we summarize the roles of glycans in the biology of NETs; on the one hand, we focus on the glycan-dependent strategies of endogenous cells to control NET formation or to inactivate its cytotoxic effects, and, on the other hand, the “sweet” tricks of pathogens to inhibit the release of NETs or to prevent NET-mediated killing mechanisms are examined. Understanding both, the forces of good and evil, allows the development of novel glycan-based approaches to combat the harmful side of NETs during distinct pathologies.